Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

For every point \((a, b)\) lying on line 1, point \((b, -a)\) lies on line 2. If the equation of line 1 is \(y = 2x + 1\) , what is the equation of line 2 ?

Find two points on line 2 and use their coordinates to build the line's equation. Points \((0, 1)\) and \((-\frac{1}{2}, 0)\) on line 1 correspond to points \((1, 0)\) and \((0, \frac{1}{2})\) on line 2. The equation of line 2 is \(\frac{y - 0}{\frac{1}{2} - 0} = \frac{x - 1}{0 - 1}\) or \(2y = 1 - x\) . The correct answer is B.

i cant understand what the formula used here for building equation line 2. Can somebody explain? what is the Formula ? thank you

The formula for finding the slope of a line is (change in y)/(change in x)

In your case, two coordinates (1,0) and (0,1/2) where (x,y)

(0-1/2)/(1-0) = -1/2 which is the slope of the line. The common formula for a line is y = kx + m where k is the slope and m is the y-intercept.

The second coordinate (0,1/2) tells us that when x = 0 y = 1/2, which is the y-intercept or 'm' in the formula y = kx+m where m is the y-intercept and 'k' is the slope. Plugging in the slope (-1/2) and the intercept (1/2) into the formula gives us y = 1/2-(x/2)

multiplying by 2 on both sides: 2y = 1-x _________________

The formula for finding the slope of a line is (change in y)/(change in x)

In your case, two coordinates (1,0) and (0,1/2) where (x,y)

(0-1/2)/(1-0) = -1/2 which is the slope of the line. The common formula for a line is y = kx + m where k is the slope and m is the y-intercept.

The first coordinate (1,0) tells us that when y = 0 x = 1, which is the y-intercept or 'm' in the formula y = kx+m where m is the intercept and 'k' is the slope. Pluggin in the slope (-1/2) and the intercept (1) into the formula gives ut y = 1-(x/2)

y- intercept is at x=0 as i know. so y= 1/2 when x=0 Am i missing something?

The formula for finding the slope of a line is (change in y)/(change in x)

In your case, two coordinates (1,0) and (0,1/2) where (x,y)

(0-1/2)/(1-0) = -1/2 which is the slope of the line. The common formula for a line is y = kx + m where k is the slope and m is the y-intercept.

The first coordinate (1,0) tells us that when y = 0 x = 1, which is the y-intercept or 'm' in the formula y = kx+m where m is the intercept and 'k' is the slope. Pluggin in the slope (-1/2) and the intercept (1) into the formula gives ut y = 1-(x/2)

y- intercept is at x=0 as i know. so y= 1/2 when x=0 Am i missing something?

Sorry, you are correct, I had a rough day yesterday I hope it makes sense now. (edited my post above) _________________

For every point \((a, b)\) lying on line 1, point \((b, -a)\) lies on line 2. If the equation of line 1 is \(y = 2x + 1\) , what is the equation of line 2 ?

Find two points on line 2 and use their coordinates to build the line's equation. Points \((0, 1)\) and \((-\frac{1}{2}, 0)\) on line 1 correspond to points \((1, 0)\) and \((0, \frac{1}{2})\) on line 2. The equation of line 2 is \(\frac{y - 0}{\frac{1}{2} - 0} = \frac{x - 1}{0 - 1}\) or \(2y = 1 - x\) . The correct answer is B.

i cant understand what the formula used here for building equation line 2. Can somebody explain? what is the Formula ? thank you

For every point \((a, b)\) lying on line 1, point \((b, -a)\) lies on line 2. If the equation of line 1 is \(y = 2x + 1\) , what is the equation of line 2 ?

Find two points on line 2 and use their coordinates to build the line's equation. Points \((0, 1)\) and \((-\frac{1}{2}, 0)\) on line 1 correspond to points \((1, 0)\) and \((0, \frac{1}{2})\) on line 2. The equation of line 2 is \(\frac{y - 0}{\frac{1}{2} - 0} = \frac{x - 1}{0 - 1}\) or \(2y = 1 - x\) . The correct answer is B.

i cant understand what the formula used here for building equation line 2. Can somebody explain? what is the Formula ? thank you

This is how I solved and it worked but I don't know why it worked :D Please enligthen me about why it worked...

I plugged in (a,b) in line 1 equeation to get b=2a+1..

then I started plugging in (b,-a) in the answer choices.. the 2nd answer choice resulted in b=2a+1.. and hence I marked B.. I am not sure why this worked.. Please help. . _________________

hope is a good thing, maybe the best of things. And no good thing ever dies.

I plugged in (a,b) in line 1 equeation to get b=2a+1..

then I started plugging in (b,-a) in the answer choices.. the 2nd answer choice resulted in b=2a+1.. and hence I marked B.. I am not sure why this worked.. Please help. .

Responding to a pm:

a and b stand for two numbers which define a co-ordinate on the plane. When you say that (a, b) lies on y = 2x+1, it means the relation between a and b is b = 2a + 1. e.g. if a = 0, b = 1; if a = 1, b = 3... At the end of the day, a line is nothing but a depiction of how one variable changes with another. A line just shows you the relation between 2 variables.

If (b, -a) lies on a line 2y = 1-x, this is just a different way of expressing the same relation between the two numbers a and b. a and b are the same set of numbers (i.e. if a = 0, b = 1; if a = 1, b = 3...) So after manipulating the equation a little, you are bound to get b = 2a + 1 only.

As you figured out, the approach is a little un-intuitive. When I looked at the problem, I actually solved it exactly the same way except that I took numbers rather than a and b.

I said, if (a, b) lies on y = 2x + 1, if a = 1, b = 3. So (3, -1) must lie on the new equation of the line. When I put (3, -1) in the options, I see that only (B) satisfies. _________________